Hepatitis B and C among patients with hidradenitis suppurativa: a population‐based study. (17th May 2021) - Cohen, Jeffrey M.; Kridin, Khalaf; Perez‐Chada, Lourdes M.; Merola, Joseph F.; Cohen, Arnon D.
Abstract: Background: Hidradenitis suppurativa (HS) is a chronic inflammatory condition related to multiple systemic diseases and infections. Methods: This retrospective cross‐sectional study from 1999 to 2015 used the database of Clalit Health Services, the largest managed care organization in Israel, to explore the association between HS and hepatitis B and C. Sociodemographic and clinical information was compared using χ 2 tests for sex and socioeconomic status and t ‐tests for age. Logistic regression was used to calculate odds ratios (ORs) and 95% confidence intervals (CIs) to compare the odds of hepatitis B and C in those with and without HS. Results: In multivariate analysis controlling for sex, age as a continuous variable, Arab ancestry, and history of drug abuse, HS was associated with a 1.87‐fold increased odds (95% CI 1.11–3.17, P = 0.019) of hepatitis B (HBV). HS was also associated with HCV in multivariate analysis controlling for sex, age per year, Arab ancestry, alcohol use, and drug use, with a 1.74‐fold increased odds (95% CI 1.05–2.89, P = 0.032) of hepatitis C (HCV) among those with HS as compared to controls. Conclusions: This study demonstrated an association between HS and both hepatitis B and hepatitis C.